Act Like A Man Challenging Masculinities in American Drama - Vorlicky, Robert (University of Michigan Press, 1995)
In the first comprehensive study of plays written for male characters only, Robert Vorlicky offers a new theory that links cultural codes governing gender and the conventions determining dramatic form. Act Like a Man looks at a range of plays, including those by O'Neill, Albee, Mamet, Baraka, and Rabe as well as new works by Philip Kan Gotanda, Alonzo Lamont, and Robin Swados, to examine how dialogue within these works reflects the social codes of male behavior and inhibits individualization among men. Plays in which women are absent are often characterized by the location of a male "other"-a female presence who distances himself from the dominant, impersonal masculine ethos and thereby becomes a facilitator of personal communication. The potential authority of this figure is so powerful that its presence becomes the primary determinant of the quality of men's interaction and of the range of male subjectivities possible. This formulation becomes the basis of an alternative theory of American dramatic construction, one that challenges traditional dramaturgical notions of realism.